Review of solvents based on biomass for mitigation of wax paraffin in Indonesian oilfield - Afdhol, M.K. (MDPI AG, 2019)
This paper presents a review of the expectations and challenges of using biomass in the prevention and slowing of paraffin wax deposition that takes place during the crude oil production process. The inhibition of the deposition process involves the use of solvents from biomass that are generally available around the crude oil production field. The processes used to scale down the precipitation of wax include mixing crude oil with the manufacturer's solvent composed of toluene and xylene. The goal is to assess solvents sourced from biomass that are capable to slow down the wax deposition process. Wax appearance temperature is an important characteristic to evaluate the possible wax precipitation of a given fluid. Wax precipitation can be reduced by using some chemical additives, often called the pour point depressant. This additive is expected to be produced from local biomass which can compete with solvents currently produced on the market. Â© 2019 by the authors.